Arts Alive: A literature review to support curriculum specification development for the area of Arts Education - O'Sullivan, Carmel; Piazzoli, Erika; Heeran Flynn, Louise; Mc Cormick, Susan (National Council for Curriculum and Assessment, 2023)
This review is drawn from extensive and systematic reviews of the literature in Arts Education; as art form, as discrete subject and as arts pedagogy. The review constitutes a narrative enquiry and as such it is a comprehensive interrogation of the relevant thinking and practice. At its core, as driving force, and through a series of critical and creative lenses is the importance of arts education in children’s learning. This is the engine of the work. As a systematic process, the working group conducted the review in parallel stages. Recent peer reviewed work, both as empirical and desk based research formed the initial scope for the review. In parallel, the research took in the grey literature deemed significant to the work; the legislation, policy and curricula documents along with practices in the field. Sequentially, the scope of the review moved into a more in-depth series of considerations and interrogations of the literature in order to argue for the significance of arts education in the Primary Curriculum.
PUBLISHED
A literature review commissioned by the NCCA to support curriculum specification development for the area of Arts Education in the new primary school curriculum to be published in 2025.
Keywords: Creative Arts Practice; Creative Technologies; Identities in Transformation; Inclusive Society; Making Ireland; Arts in Education; Continuing Professional Development; Early Years Education; Education policy; Inclusive Education; Teacher Education; Autistic Spectrum disorders; Emotional-behavioural Problems; Intellectual Disability; Accessibility; Children; Education; Policy; Social participation; Youth